Resilient Intrusion Tolerance through Proactive and Reactive Recovery - Sousa, Paulo (2007)
Previous works have studied how to use proactive recovery to build intrusion-tolerant replicated systems that are resilient to any number of faults, as long as recoveries are faster than an upper-bound on fault production assumed at system deployment time. In this work, we propose a complementary approach that combines proactive recovery with services that allow correct replicas to react and recover replicas that they detect or suspect to be compromised. One key feature of our proactive-reactive recovery approach is that, despite recoveries, it guarantees the availability of the minimum amount of system replicas necessary to sustain system's correct operation. We design a proactive-reactive recovery service based on a hybrid distributed system model and show, as a case study, how this service can effectively be used to augment the resilience of an intrusion-tolerant firewall adequate for the protection of critical infrastructures